PENINGKATAN SISTEM INFORMASI GEOGRAFIS DALAM PENENTUAN EFISIEN RUTE PERJALANAN WISATA - Hermansyah, Hermansyah (Scenario (Seminar of Social Sciences Engineering and Humaniora), 2021)
Doing a tour independently without using travel services, of course, users must know the desired tourist destinations. Tourists often have problems finding a way to get to the destination tourist location. This study aims to facilitate travel in finding efficient travel routes that can be taken in the tourist areas of Karo Regency. The method used in this research is the Floyd Warshall Algorithm method for solving the search for the shortest route. The results of the research show that the geographic information system for determining efficient travel routes based on android can make it easier for users to get information about tourism in Karo district based on categories of cultural tourism, natural tourism and culinary tourism, and displays the shortest travel route from the user's location to the location. tourist destination. So that the geographic information system for determining efficient travel routes based on android can make it easier for users to access destination tourist locations quickly and precisely (efficiently).